Предмет: Математика,
автор: olgaedinorog
Помогите решить ,пожалуйста 2-х/х^2+3х + 6/х^2-9 = 1/х-3
Ответы
Автор ответа:
0
(2-x)/[x(x+3)+6/[(x-3)(x+3)]=1/(x-3)
x≠-3,x≠3,x≠0
(2-x)(x-3)+6*x-1*(x²+3x)=0
2x-6-x²+3x+6x-x²-3x=0
-2x²+8x-6=0
x²-4x+3=0
x1+x2=4 U x1*x2=3
x1=1
x2=3 не удов усл
Ответ х=1
x≠-3,x≠3,x≠0
(2-x)(x-3)+6*x-1*(x²+3x)=0
2x-6-x²+3x+6x-x²-3x=0
-2x²+8x-6=0
x²-4x+3=0
x1+x2=4 U x1*x2=3
x1=1
x2=3 не удов усл
Ответ х=1
Похожие вопросы
Предмет: Математика,
автор: Ann2011ss
Предмет: Алгебра,
автор: Аноним
Предмет: Биология,
автор: banceranastasia40
Предмет: Алгебра,
автор: torikutukova
Предмет: Математика,
автор: sibaevaroza